MORALCULTURE OF SENIOR PUPILS: CHARACTER AND UPBRINGING SUGGESTIONS - Girdzijauskas, Arvydas (Acta Paedagogica Vilnensia, 2008)
This article discusses the concept of moral culture of senior pupils and presents character of it’s manifestation. The components of moral culture are analyzed on the basis of empirical research. The investigation of moral culture was based on the ideas of cognitive anthropology, cultural, existential and hermeneutic philosophy.The object of research was determined as the character of moral culture of senior pupils.The aim of research – to reveal character of moral culture of senior students.Moral culture is understood as unity of moral consciousness with the kind of behavior, based on internalization of moral codes, enabling successful activity of individual in its cultural surrounding. Character and expression of moral culture, as well as its relations to gender and quality of studies of senior pupils were investigated. 390 senior pupils from different types of schools took part in the research. The research data showed, that pupils recognize the importance of moral values, but their ability to evaluate situations and behavior is not mature, as less than half of the students showed high level of validity and contextuality of their evaluations. The analysis of the emotional component revealed, that pupils like emotions, which are related to moral values. The ability of decision making is closely related to stability of moral behavior. High level of independence in decision making was revealed. However, not all moral values are implemented in moral behavior. That means, that the maturity of moral culture of higher grade students is not high. The assumption, that increasing of level of evaluation ability can influence decision making and moral behavior of senior pupils was made. Salience of independent deci- sion making revealed the importance of personal identity of students to their moral culture. Possible influence of surrounding atmosphere on moral culture was found, as pupils are prone to tune to surrounding conditions. The investigation showed, that girls and successful students are of more mature moral culture.
Keywords: moral culture; moral values; moral behavior